Does music training provide non-musical benefits? Evidence from auditory, linguistic, and socio-emotional processing - Neves, L.; Martins, M.; Correia, A. I.; Martins, D.; Draganski, B.; Castro, S. L.; Lima, C. F. (23° CONFERENCE OF THE EUROPEAN SOCIETY FOR COGNITIVE PSYCHOLOGY, 2023)
There is a growing body of research on the effects of music training. While near transfer effects to domains tightly related to music are often taken for granted, the evidence about potential far transfer to non-musical domains remains controversial. Given the tight association between music, cognitive and socio-emotional processing we sought to fill in this knowledge gap by focusing on the following points: (1) a meta-analysis of longitudinal studies on neurobehavioral effects of music training on auditory and linguistic processing, in which we found a small positive neurobehavioral enhancement of music training on both domains; (2) a cross- sectional study analyzing associations between children’s emotion recognition skills and socio-emotional adjustment, showing that higher emotion recognition in prosody relates to better socio- emotional adjustment; and (3) a longitudinal study inspecting music training effects on near transfer domains, and a wide range of socio- emotional abilities. The observed near transfer to auditory and motor skills was not paralleled by far transfer to socio-emotional processing. This led us to conclude that the empirical evidence for far transfer in musical training is non-existent or weak at best.